Pooled human bone marrow-derived mesenchymal stromal cells with defined trophic factors cargo promote dermal wound healing in diabetic rats by improved vascularization and dynamic recruitment of M2-like macrophages - Willer, Hélène; Spohn, Gabriele; Morgenroth, Kimberly; Thielemann, Corinna; Elvers-Hornung, Susanne; Bugert, Peter; Delorme, Bruno; Giesen, Melanie; Schmitz-Rixen, Thomas; Seifried, Erhard; Pfarrer, Christiane; Schäfer, Richard; et al. (Frontiers in Immunology, 2022)
This Abstract cannot be displayed